El Sistema Férreo Como Dinamizador Del Comercio Exterior En Colombia (2023)
Colombia has witnessed the disadvantages of not having a sustainable infrastructure and managing an intermodal transportation system articulated by railways, in order to move cargo for internal and external consumption, considering that the country is rich in various products among which is coal, followed by cement, some of the other products that are transported are steel, scrap metal and coffee beans.